THE ROLE OF MEDIATION IN RESOLVING INTERNATIONAL AND REGIONAL CONFLICTS: PROBLEMS AND SOLUTIONS (Symposium on Natural and Applied Sciences, 2026)
This article examines the role of mediation in resolving international and regional conflicts. It analyzes the effectiveness of mediation as a peaceful dispute resolution mechanism and highlights its importance in maintaining global and regional stability. The study discusses the main challenges faced in mediation processes, such as lack of trust between conflicting parties, political pressure, and insufficient legal frameworks. It also proposes possible solutions, including strengthening international legal institutions, increasing the role of neutral mediators, and enhancing diplomatic dialogue. The research emphasizes that mediation is one of the most effective tools for preventing escalation and achieving sustainable peace.
Keywords: mediation, international conflicts, regional conflicts, conflict resolution, diplomacy, peacebuilding, negotiation, international law, dispute settlement, stability